Bulk Hydrogen Analysis of Cyanogenic Food Plants Using Neutrons for Routine Quality Control - Garba, Keziah; Jonah, Sunday; Onyike, Elewechi (My University, 2023)
Millions face food safety threats, with 70% of rural African staples like cocoyam and sorghum harbouring toxic cyanogenic glycosides. To ensure safe consumption, we employed neutron reflection, a rapid, sustainable technique, to assess hydrogen content, which inversely correlates with cyanide levels. This non-destructive approach proved effective, paving the way for routine food quality control and improved public health through the innovative application of particle radiation technology.
Keywords: Neutron Reflection; Food security; quality control measures